Case report: Pathological complete response of pregnancy associated pulmonary enteric adenocarcinoma to chemoradiotherapy - Nemoto, Yukiko; Kuroda, Koji; Oyama, Rintaro; Mori, Masataka; Shimajiri, Shohei; Tanaka, Fumihiro (Frontiers in Oncology, 2024)
Pulmonary enteric adenocarcinoma (PEAC) is a rare lung adenocarcinoma with morphological features similar to those of primary and metastatic colorectal adenocarcinoma. To date, only a few studies have reported the therapeutic effects of chemoradiotherapy on PEAC. This report describes the case of a 28-year-old woman with pregnancy-related PEAC who presented with left shoulder pain. A superior sulcus tumor was identified in the left thoracic cavity, and the biopsy indicated more than 50% intestinal differentiation components. Moreover, immunohistochemical staining revealed positive CDX2 and CK7 expression. Positron emission tomography-computed tomography, upper endoscopy, colonoscopy, and small intestinal capsule endoscopy revealed no gastrointestinal malignancies. The patient was diagnosed with locally advanced PEAC (clinical stage T4N0M0; stage IIIA). Therefore, the patient was treated with preoperative chemoradiotherapy and underwent gross total resection during surgery. Pathological evaluation of the specimen revealed no residual tumor, indicating that the chemoradiotherapy for PEAC was highly effective. One subsequent brain metastasis was also resected, and the patient has not experienced recurrence in 28 months since this resection and continues to be monitored regularly. This is the first pathologically confirmed report of the use of chemoradiotherapy (carboplatin [CBDCA] and paclitaxel [PTX]) for PEAC and its clinical efficacy. Unlike previous reports, the efficacy of this treatment is attributed to the use of PTX in preoperative chemotherapy and the p21-status of the patient, which may have increased sensitivity to chemoradiation therapy. Therefore, chemoradiotherapy (CBDCA + PTX) may be a viable treatment option for advanced intestinal lung adenocarcinoma.